A visualized pulmonary arterial thrombus by using a modified echocardiographic view in an intermediate‐risk acute pulmonary embolism patient: A case report. Issue 7 (19th July 2022) - Mu, Guanyu; Li, Feixue; Chen, Xiaolin; Zhao, Bo; Li, Guangping; Fu, Huaying
Abstract: Acute pulmonary embolism (APE) is a life‐threatening disease with nonspecific clinical signs and symptoms. Rapid and accurate diagnosis is crucial for the clinical management of patients with acute pulmonary embolism. A recommended echocardiography view may be of further help in the diagnosis and evaluation of the change in thrombosis and treatment. We reported a case of a 74‐year‐old man with a 12‐day history of decreased exercise capacity and dyspnea. The patient was diagnosed with intermediate‐risk APE as several pulmonary emboli in pulmonary artery were seen in multidetector computed tomographic pulmonary angiography with normal blood pressure and echocardiographic right ventricular overload. And we found a pulmonary artery clot in the right pulmonary artery through transthoracic echocardiography. After 11‐days anticoagulation, the patient underwent a reassessment, showed a decrease in RV diameter and pulmonary artery thrombus. This case highlights the significant role that echocardiography played in a patient who presented pulmonary embolism with a stable hemodynamic situation and normal blood pressure. The modified echocardiographic view could provide correct diagnosis by identifying the clot size and location visually. Knowledge of the echocardiography results of APE would aid the diagnosis. Abstract : We reported a patient diagnosed intermediate‐risk APE. A pulmonary artery clot in the right pulmonary artery was found through a modified TTE view. And the view could provide correct diagnosis by identifying the clot size and location visually.